Research progress on the mutual regulatory mechanism of circadian clock genes and autophagy - Ma, Yueqi; Yu, Ran; Zheng, Xueqing; Rao, Jiahui; Shi, Gaiping; Ding, Yumei (Frontiers in Cell and Developmental Biology, 2025)
Recent studies have highlighted the intricate relationship between the circadian rhythm, a natural biological process responsive to light and darkness, and autophagy, a mechanism crucial for maintaining cellular homeostasis. Circadian clock genes, which are pivotal in regulating our internal body clock, appear to be closely intertwined with autophagy. These genes can directly influence the expression of autophagy-related genes or modulate signalling pathways that govern autophagic processes. Conversely, autophagy also controls the expression and activity of circadian clock genes. Investigating these interactions will help elucidate how autophagy and circadian rhythms maintain cellular equilibrium and regulate physiological functions. Moreover, such studies help reveal disease mechanisms and develop potential therapeutic strategies.